A Systematical Review of The Effect of Ketogenic Diet on Bcl-2 (B-cell lymphoma-2) Expression as An Apoptosis Marker in Cancer Treatment - Vania Islamey Kusuma; Reny I’tishom; Ema Qurnianingsih; Purwo Sri Rejeki (Biomolecular and Health Science Journal, 2021)
Introduction: Ketogenic diet seems to be in a great demand nowadays as a lot of people are interested in adopting it into their lifestyle. It is also found that the ketogenic diet shows several beneficial effects including cancer prevention. However, the detail mechanism still remains unknown. Therefore, this review was aimed to find out the effect of ketogenic diet on Bcl-2 (B-cell lymphoma-2) expression in cancer.Methods: We searched published literatures in PubMed through 2011-2020 using specific keywords. The literatures were filtered according to inclusion and exclusion criteria. Animal model, total sample size, underlying condition/inflammatory process occurs, details of the intervention/diet including diet contents in control group and high-fat group, and the duration of the intervention, Bcl-2 results, and p-value were extracted.Results: 7 studies were included in this review. Bcl-2 expression found decrease in 5 out of 6 studies. Similar result also obtained in Bcl-2 protein level, which measured by western blot. Bcl-2 protein level shows a decrease in 2 out of 3 studies.Conclusion: This review shows that high-fat diet that contained in ketogenic diet most likely lead to decrease in Bcl-2 expression. Therefore, indicating the ability of ketogenic diet to affect cancer progression by inducing apoptosis process.